EDUPRENEURS’ INNOVATION AND CREATIVITY IN DEVELOPING TEACHERS' BOOK PLANNERS TO ENHANCE THE PEDAGOGICAL COMPETENCE OF EARLY CHILDHO OD TEACHERS - Nurhayati, Sri; Kristiyanti, Leni (Universitas Al-Hikmah Indonesia, 2024)
The purpose of this research is to explore how edupreneurs identify and incorporate the needs and preferences of PAUD teachers in the development of innovative and effective Teachers' Book Planners, assess the impact of these planners on the pedagogical competence of PAUD teachers and the learning outcomes of children, and examine the key challenges they face in production and distribution. The method used is qualitative case study. Data collected through semi-structured interviews and observations with three edupreneurs and ten Islamic PAUD educators were analyzed using thematic analysis, employing triangulation, member checking, and peer debriefing to ensure validity and reliability. The research found that edupreneurs identify and incorporate the needs and preferences of PAUD teachers through detailed user research, continuous feedback collection, and iterative design processes. By addressing both practical and innovative aspects, they develop effective Teachers' Book Planners that enhance the pedagogical experience. Ongoing improvement and adaptation based on user feedback ensure that these planners remain relevant and beneficial in the educational context. Edupreneurs face multifaceted challenges in the production and distribution of Teachers' Book Planners including ensuring the quality and availability of raw materials, managing the production process, controlling costs, handling logistics, collaborating with vendors, adopting new technologies, and maintaining sustainability and regulatory compliance. This research contributes to the existing body of knowledge by providing insights into the specific needs and preferences of PAUD teachers and the practical challenges faced by edupreneurs in developing educational tools.